Distinguishing between biochemical and cellular function: Are there peptide signatures for cellular function of proteins?. Issue 4 (6th February 2017) - Jain, Shruti; Bhattacharyya, Kausik; Bakshi, Rachit; Narang, Ankita; Brahmachari, Vani
ABSTRACT: The genome annotation and identification of gene function depends on conserved biochemical activity. However, in the cell, proteins with the same biochemical function can participate in different cellular pathways and cannot complement one another. Similarly, two proteins of very different biochemical functions are put in the same class of cellular function; for example, the classification of a gene as an oncogene or a tumour suppressor gene is not related to its biochemical function, but is related to its cellular function. We have taken an approach to identify peptide signatures for cellular function in proteins with known biochemical function. ATPases as a test case, we classified ATPases (2360 proteins) and kinases (517 proteins) from the human genome into different cellular function categories such as transcriptional, replicative, and chromatin remodelling proteins. Using publicly available tool, MEME, we identify peptide signatures shared among the members of a given category but not between cellular functional categories; for example, no motif sharing is seen between chromatin remodelling and transporter ATPases, similarly between receptor Serine/Threonine Kinase and Receptor Tyrosine Kinase. There are motifs shared within each category with significant E value and high occurrence. This concept of signature for cellular function was applied to developmental regulators, the polycomb and trithorax proteins which led to the prediction of the role of INO80, a chromatin remodelling protein, in development. This has been experimentally validated earlier for its role in homeotic gene regulation and its interaction with regulatory complexes like the Polycomb and Trithorax complex. Proteins 2017; 85:682–693. © 2016 Wiley Periodicals, Inc.